286 Sex cord-stromal tumour with rhadomyosarcomatous contingent heterologous in A 7-year-old girl treated for xeroderma pigmentosum. (18th September 2019) - Bacha, D; Ben Amor, A; Sassi, A; Saffar, K; Lahmar, A; Bouraoui, S; Ben Slama, S
Abstract : Objectives: To report the first case of Sex cord-stromal tumour with rhadomyosarcomatous contingent heterologous in a 7-year-old girl with history of xeroderma pigmentosum (XP). Methods: We report the clinical data, imaging investigations, and outcome data of a 7-year-old girl treated for XP. We used the fourth edition of the WHO classification of tumors of female reproductive organs for pathological study. Results: A 7-year-old girl with history of XP was présented with a large 12x7 cm ovarian tumor associated with ascites and general deterioration. Radiological investigations confirm the presence of the tumor which was unilateral and does not appear to infiltrate the surrounding tissues The patient was operated by laparotomy The diagnosis of sex cord-stromal tumour with rhadomyosarcomatous contingent heterologous could not be made in the frozen section. The final examination confirms the diagnosis. Chemotherapy was scheduled but the patient died a few weeks after the surgery. Conclusions: Ovarian tumors are exceptionally associated with XP. They present a particular histological and evolutionary profile. Their pathogenesis and their management is not codified due to the rarity of this entity.